On the distribution of links in the interbank network: Evidence from the e-mid overnight money market - Daniel Fricke; Thomas Lux (Kiel Institute for the World Economy (IfW), 2013)
Previous literature on statistical properties of interbank loans has reported various power-laws, particularly for the degree distribution (i.e. the distribution of credit links between institutions). In this paper, we revisit data for the Italian interbank network based on overnight loans recorded on the e-MID trading platform during the period 1999-2010 using both daily and quarterly aggregates. In contrast to previous authors, we find no evidence in favor of scale-free networks. Rather, the data are best described by negative Binomial distributions. For quarterly data, Weibull, Gamma, and Exponential distributions tend to provide comparable fits. We find comparable results when investigating the distribution of the number of transactions, even though in this case the tails of the quarterly variables are much fatter. The absence of power-law behavior casts doubts on the claim that interbank data fall into the category of scale-free networks.
Keywords: G21; G01; E42; 330; interbank market; network models